PENGARUH EARNING PER SHARE, PRICE EARNING RATIO, UKURAN PERUSAHAAN (FIRM SIZE), RISIKO SISTEMATIS (BETA) TERHADAP RETURN SAHAM (Studi Pada Perusahaan Real Estate & Property yang Terdaftar di Bursa Efek Indonesia) - Sabet Silalahi, Eli; Putri Purba, Riski Ananda; Sihombing, Lorisa; Fahada, Nazli (EDUTECH CONSULTANT, 2019)
This study aims to determine The Effect of Earning Per Share, Price Earning Ratio, Firm Size, Systematic Risk on The Stock Returns in Real Estate & Property Company Listed in Indonesia Stock Exchage 2013-2016. The Population used in this study is the Real Estate & Property Company Listed in Indonesia Stock Exchage 2013-2016. The sample used in this study as money as 31 companies using purposive sampling method. Testing the hypothesis in this study using multiple linear regression analysis, t test, F test and coefficient of determination. The results showed that partially Earnings Per Share and Price Earning Ratio positive and significant influence on the Stock Returns in Real Estate and Property Companies Listed on The Indonesia Stock Exchange in 2013-2016, Firm Size negative no significant influence on the Stock Returns in Real Estate and Property Companies Listed on The Indonesia Stock Exchange in 2013-2016, while Systematic Risk negative and significant influence on the Stock Returns in Real Estate and Property Companies Listed on The Indonesia Stock Exchange in 2013-2016.